How do staff influence the quality of long-term dementia care and the lives of residents? A systematic review of the evidence. (15th April 2016) - Anderson, Katrina; Bird, Mike; MacPherson, Sarah; Blair, Annaliese
ABSTRACT: Background: Research suggests and common sense indicates that there are relationships between staff variables in residential dementia care and the quality of life (QOL) of residents, with poor care due to staff factors increasing resident suffering. Despite these indications, we do not have a coherent picture of these relationships, which variables are important, and where to intervene in order to minimize suffering for people with dementia. Methods: This systematic review examined associations between staff variables, quality of care (QOC), and QOL for residents, using published peer-reviewed literature from the last 20 years. A comprehensive search was conducted using an exhaustive list of search terms, leading to the identification of 33, 204 unique papers, which was reduced to 35 on-topic papers. Results: In the main, we were able to provide collective evidence to suggest there are relationships between potentially adjustable staff variables and QOC on to QOL. When staff treat and interact empathetically and humanely in care, there is a relationship with better mood for residents, delayed functional dependence and better food intake. Where staff are more skilled and educated, there is less psychotropic medication use. Unlimited empathy about the risk of residents falling or being in pain is not enough; staff need to know about the dangers of restraint. Conclusions: Confidence in these indicative links is weakened by a lack of high-quality prospective longitudinal studies focusing on potentially adjustable staff variables, with a bias towards cross-sectional studies including only variables that are fixed or unlikely to change. (Review registration no. PROSPERO 2014:CRD42014015224).